Phytoplankton Diversity and Distribution in Relation to Hydro Biological Factors in Three Industrial Hotspots of the Northern Gulf of Kachchh, Gujarat, India - Hitesh, Kardani; Mankodi, P C; Thivakaran, G A (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Phytoplankton serve as crucial indicators of environmental health, reflecting changes in water quality. By monitoring water quality parameters, we can assess the overall status of the coastal/marine ecosystem hence the diversity, distribution, and abundance of phytoplankton and their relationship to hydro-biological factors were investigated at three industrial hotspots in the Northern Gulf of Kachchh. The density of phytoplankton species ranged from 237*103 to 1115*103 No/lit. The Shannon wiener diversity index, Margalef richness index, and Pielou's evenness index, respectively, were 2.498 to 3.746, 4.941 to 7.531 and 0.259 to 0.9 during the study. 78 taxa from three phyla and three classes were reported throughout the study period. Chaetoceros was the most dominant genus among other groups. The study was carry out for 2 years and planktons were collected from study sites by using plankton net. During all seasons, taxa such as Fragilariopsis oceanica, Nitzschia sp, Biddulphia sp, Asterionella japonica, Ditylum sol, Pleurosigma sp, and Trieres mobiliensis were documented from all sites during all seasons. The influence of dissolved oxygen, turbidity, temperature, salinity, pH, total suspended solid, nitrites, nitrates, and phosphate on plankton distribution and abundance has been discussed. The areas were selected based on the presence of industrial establishments, coastal characteristics and the study will serve as a baseline database for future research. The various industrial activities may have adverse effect on the plankton diversity.